Essential competencies in prescribing: A first european cross‐sectional study among 895 final‐year medical students. Issue 2 (17th November 2016) - Brinkman, DJ; Tichelaar, J; Schutte, T; Benemei, S; Böttiger, Y; Chamontin, B; Christiaens, T; Likic, R; Maˇiulaitis, R; Marandi, T; Monteiro, EC; Papaioannidou, P; et al.
Abstract : European medical students should have acquired adequate prescribing competencies before graduation, but it is not known whether this is the case. In this international multicenter study, we evaluated the essential knowledge, skills, and attitudes in clinical pharmacology and therapeutics (CPT) of final‐year medical students across Europe. In a cross‐sectional design, 26 medical schools from 17 European countries were asked to administer a standardized assessment and questionnaire to 50 final‐year students. Although there were differences between schools, our results show an overall lack of essential prescribing competencies among final‐year students in Europe. Students had a poor knowledge of drug interactions and contraindications, and chose inappropriate therapies for common diseases or made prescribing errors. Our results suggest that undergraduate teaching in CPT is inadequate in many European schools, leading to incompetent prescribers and potentially unsafe patient care. A European core curriculum with clear learning outcomes and assessments should be urgently developed.